Cross-disease spillover from research funding: Evidence from four diseases - Coburn, Josie; Yaqub, Ohid; Ràfols, Ismael; Chataway, Joanna (Social science & medicine (1982), 2024)
There is widespread appreciation for the role of research in addressing health problems. However, there is limited evidence on the extent to which research can be targeted to specific diseases. Analyses highlighting a concentration of research funding towards certain diseases have prompted growing scrutiny over the allocation of research funding. In this paper, we show that research funding targeted to a disease often results in publications relating to other diseases. Using data from the world's largest biomedical research funders, we estimated the frequency and direction of this cross-disease spillover by examining 337,573 grant–publication pairs for four diseases. We found the majority of our grant–publication pairs were cross-disease spillovers. We also found some variation between “rich” and “poor” diseases, in terms of the frequency and direction of cross-disease spillover. These differences are likely to be related to characteristics of the diseases themselves, as well as features of the research environment. One implication of frequent cross-disease spillover is that although more investment in areas of research such as neglected diseases is necessary, it may not be sufficient to improve the alignment between research funding and health needs. •The organisation of medical research funding is increasingly disease-focused.•We explored whether such efforts contribute to non-focal diseases.•We mapped 337,573 publications from a sample of grants for 4 disease foci.•We found variation in frequency and direction of cross-disease spillovers.•Focusing on disease is one of way to improve health, but there are other ways too.